CD8+ T-cells contribute to lesion stabilization in advanced atherosclerosis by limiting macrophage content and CD4+ T-cell responses. Issue 4 (18th October 2018) - van Duijn, Janine; Kritikou, Eva; Benne, Naomi; van der Heijden, Thomas; van Puijvelde, Gijs H; Kröner, Mara J; Schaftenaar, Frank H; Foks, Amanda C; Wezel, Anouk; Smeets, Harm; Yagita, Hideo; Bot, Ilze; et al.
Abstract: Aims: T lymphocytes play an important role in atherosclerosis development, but the role of the CD8 + T-cell remains debated, especially in the clinically relevant advanced stages of atherosclerosis development. Here, we set out to determine the role of CD8 + T-cells in advanced atherosclerosis. Methods and results: Human endarterectomy samples analysed by flow cytometry showed a negative correlation between the percentage of CD8 + T-cells and macrophages, suggesting a possible protective role for these cells in lesion development. To further test this hypothesis, LDLr −/− mice were fed a western-type diet (WTD) for 10 weeks to induce atherosclerosis, after which they received CD8α-depleting or isotype control antibody for 6 weeks. Depletion of CD8 + T-cells in advanced atherosclerosis resulted in less stable lesions, with significantly reduced collagen content in the trivalve area, increased macrophage content and increased necrotic core area compared with controls. Mechanistically, we observed that CD8 depletion specifically increased the fraction of Th1 CD4 + T-cells in the lesions. Treatment of WTD-fed LDLr −/− mice with a FasL-neutralizing antibody resulted in similar changes in macrophages and CD4 + T-cell skewing as CD8 + T-cell depletion. Conclusion: These findings demonstrate for the first time a local, protective role for CD8 + T-cells in advanced atherosclerosis, through limiting accumulation of Th1 cells and macrophages, identifying a novel regulatory mechanism for these cells in atherosclerosis.